Pengaruh Gaya Komunikasi Pendidikan dalam Proses Pembelajaran: Studi Kasus Gaya Mengajar Terhadap Minat dan Peningkatan Kompetensi Mahasiswa pada Universitas Islam Negeri Ar-Raniry - Zainuddin T (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The purpose of this research is to explore the influence of educational communication styles in conducting the learning process in State Islamic University students on interest and competence. This research uses qualitative research methods with an analytical descriptive approach. From the results of the research conducted, it was found that lecturers in teaching use the lecture method, presentations and tend to sit in chairs and do not move much. There are also lecturers who teach using interactive learning, modern and focused on the study so that this kind of model is interesting and makes students want to learn